Strategi Peningkatan Kompetensi dan Kinerja SDM Karyawan Toko Handphone - Khotimah, Aulia Khusnul; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the quality of human resources among mobile phone store employees in Bawen, Semarang Regency. The problem is focused on three main aspects, namely customer service, product knowledge, and digital marketing skills, which are considered influential in enhancing business competitiveness. To approach this problem, the study refers to theories of human resource management, marketing, and service communication. Data were collected through field observations, in-depth interviews with employees and store owners, as well as documentation related to the marketing strategies applied. All data were analyzed qualitatively through reduction, presentation, and conclusion drawing. The results show that customer service is the dominant aspect, as it determines customer satisfaction and loyalty, while product knowledge plays an important role in building consumer trust by providing detailed information on product specifications and benefits. Meanwhile, digital marketing, although less dominant, remains essential as a tool to expand marketing reach in the digital transformation era. This study concludes that the success of mobile phone stores in Bawen is not solely determined by sales ability, but rather by the integration of quality customer service, adequate product knowledge, and the sustainable use of digital technology as a marketing strategy.